Peran Penuntut Umum Terhadap Pemenuhuan Restitusi Anak Korban Tindak Pidana Kekerasan Seksual - Deanova, Luthfie Arya; Sulistiani, Lies; Ramadhani, Rully Herdita (Legal Standing : Jurnal Ilmu Hukum, 2025)
Sexual violence crimes not only affect adults as victims but also targetand impact children. Concern over the high number of sexual crimes experienced by children should not solely focus on punishing the perpetrators but also on fulfilling the rights of child victims of criminal acts. One way to restore the condition of child victims of sexual violence is through restitution. In cases of sexual crimes against children, the Public Prosecutor (JPU) plays a central role in ensuring the fulfillment of the victim's right to restitution. The central role of the Public Prosecutor in providing restitution is stated in Government Regulation No. 43 of 2017. This study aims to examine the urgency of the Public Prosecutor's role in fulfilling restitution rights and to identify the challenges and efforts in the process of fulfilling these rights for child victims. This research uses a normative juridical approach. The findings indicate that filing for restitution for child victims of sexual violence crimes is crucial and should be included in the Public Prosecutor's indictment as a form of legal protection for the child victims. However, the implementation of restitution requests in the indictment still faces obstacles, both from within the prosecutor's office and from external institutions.